Analysis of diaphragm movement during tidal breathing and during its activation while breath holding using MRI synchronized with spirometry - Kolar, P; Neuwirth, J; Sanda, J; Suchanek, V; Svata, Z; Volejnik, J; Pivec, M (Physiological research, 2009)
Using magnetic resonance imaging (MRI) in conjunction with synchronized spirometry we analyzed and compared diaphragm movement during tidal breathing and voluntary movement of the diaphragm while breath holding. Breathing cycles of 16 healthy subjects were examined using a dynamic sequence (77 slices in sagittal plane during 20 s, 1NSA, 240x256, TR4.48, TE2.24, FA90, TSE1, FOV 328). The amplitude of movement of the apex and dorsal costophrenic angle of the diaphragm were measured for two test conditions: tidal breathing and voluntary breath holding. The maximal inferior and superior positions of the diaphragm were subtracted from the corresponding positions during voluntary movements while breath holding. The average amplitude of inferio-superior movement of the diaphragm apex during tidal breathing was 27.3+/-10.2 mm (mean +/- SD), and during voluntary movement while breath holding was 32.5+/-16.2 mm. Movement of the costophrenic angle was 39+/-17.6 mm during tidal breathing and 45.5+/-21.2 mm during voluntary movement while breath holding. The inferior position of the diaphragm was lower in 11 of 16 subjects (68.75 %) and identical in 2 of 16 (12.5 %) subjects during voluntary movement compared to the breath holding. Pearson's correlation coefficient was used to demonstrate that movement of the costophrenic angle and apex of the diaphragm had a linear relationship in both examined situations (r=0.876). A correlation was found between the amplitude of diaphragm movement during tidal breathing and lung volume (r=0.876). The amplitude of movement of the diaphragm with or without breathing showed no correlation to each other (r=0.074). The movement during tidal breathing shows a correlation with the changes in lung volumes. Dynamic MRI demonstrated that individuals are capable of moving their diaphragm voluntarily, but the amplitude of movement differs from person to person. In this study, the movements of the diaphragm apex and the costophrenic angle were synchronous during voluntary movement of the diaphragm while breath holding. Although the sample is small, this study confirms that the function of the diaphragm is not only respiratory but also postural and can be voluntarily controlled.
Keywords: referenční hodnoty; Magnetic Resonance Imaging; svalová kontrakce; magnetická rezonanční tomografie; Humans; mechanika dýchání; Lung Volume Measurements; lidé středního věku; Muscle Contraction; Respiration; měření objemu plic; Female; mladý dospělý; dospělí; Pressure; tlak; lidé; Electromyography; Adult; dýchání; relaxace svalu; Spirometry; ženské pohlaví; Respiratory Mechanics; Male; Middle Aged; bránice; spirometrie; Young Adult; Reference Values; Diaphragm; mužské pohlaví; vůle; Muscle Relaxation; elektromyografie; Volition